Point Blank: A Retrospective Review of Self-inflicted Gunshot Wounds to the Hand. (March 2023) - Starr, Brian W.; Dembinski, Douglas R.; Yuan, Frank; Lax, Elizabeth A.; Yalamanchili, Suma; Megee, David M.
Background: A paucity of literature exists specifically examining self-inflicted (SI) gunshot wounds (GSWs) to the hand and wrist, which impart greater energy and have a higher risk of adverse events than non–self-inflicted (NSI) GSWs. Methods: We retrospectively reviewed records of patients who presented to our plastic surgery service after sustaining acute GSWs involving the hand and wrist between 2016 and 2018. Results: We identified 60 patients who sustained GSWs involving the hand and wrist; 17 (28%) were SI, and 43 (72%) were NSI. Within the SI group, 100% of patients were Caucasian, with an average age of 54 years. Within the NSI cohort, 77% of patients were Black, 19% were Caucasian, and 4% identified as other. While not statistically significant, we noted a substantial increase in patients requiring operative intervention in the SI cohort (65% SI vs 37% NSI, P = .08). There was a statistically significant increase in patients requiring more than 1 operation in SI patients (24% SI vs 5% NSI, P = .04). Patients who sustained SI injuries were also more likely to present with acute carpal tunnel syndrome requiring urgent surgical release and to develop wound infections (12% vs 0%, P = .08). Conclusions: Self-inflicted GSWs involving the hand and wrist are associated with greater morbidity than their low-energy NSI counterparts. Individuals presenting with SI GSWs are more likely to be older, to require multiple operations, to develop infections, and to present with acute carpal tunnel syndrome requiring urgent surgical decompression.